Beyond the Mind: The Cognitive Functions of Religious Artefacts - Sztajer, Sławomir (Człowiek i Społeczeństwo, 2025)
The role of material artifacts in religion is significant, yet they are often overlooked or underappreciated, particularly in their function of mediating religious cognition. From this perspective, they are not only tools for action, but also for religious thinking. It can be argued that some forms of religious thought are dependent on the use of material objects, which play a considerable role in cognitive processing. In this paper, I will present an argument based on the concept of extended cognition. This is a hypothesis that the processes that constitute human cognition are not confined solely to the brain or body but can extend into the external environment. I will demonstrate that there are a multitude of ways in which material artifacts are utilized in the cognitive processes that underpin religious thinking, and that a vast array of cognitive functions performed by artifacts. Among the latter are such functions as transforming mental representations into public representations and expanding the capacity of biological memory by creating external forms of memory. Additionally, there are less obvious functions, including promoting the creation of new and stabilizing existing mental representations, giving concrete form to abstract and often incompletely understood ideas, and producing a sense of the presence of intangible supernatural beings and powers. Some of these functions will be illustrated using examples from the holy books of literate cultures.